2006
DOI: 10.1093/jpepsy/jsj108
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Reading Skills Among Very-Low-Birthweight Children: Is There a Catch-up?

Abstract: The results suggest that VLBW children display positive changes over time in reading skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 27 publications
3
45
3
3
Order By: Relevance
“…[39][40][41] Furthermore, the temporal trends have shown a relatively constant gap in neuropsychological skills between preterm and term children. 26,27,42,43 Our outcome data can be compared with recent reports in showing similar estimates of risks associated with either ultrasonographic evidence of brain injury or severe ROP in children born extremely preterm or with extremely low birth weight. 1,2,6,28 Thus, we believe that our study provides valid analyses of the relation of the major neonatal morbidities such as severe ROP and brain injury to a poor outcome or functional limitation and special health care needs at 11 years, unless superseded by more recent data.…”
Section: Discussionsupporting
confidence: 51%
“…[39][40][41] Furthermore, the temporal trends have shown a relatively constant gap in neuropsychological skills between preterm and term children. 26,27,42,43 Our outcome data can be compared with recent reports in showing similar estimates of risks associated with either ultrasonographic evidence of brain injury or severe ROP in children born extremely preterm or with extremely low birth weight. 1,2,6,28 Thus, we believe that our study provides valid analyses of the relation of the major neonatal morbidities such as severe ROP and brain injury to a poor outcome or functional limitation and special health care needs at 11 years, unless superseded by more recent data.…”
Section: Discussionsupporting
confidence: 51%
“…Immaturity and related complications may entail adverse, long-term impact on child development. Cognitive, educational, and behavioural difficulties at school age are often reported [3], although, developmental progress and catch-up have been documented in recent longitudinal studies of cognitive development [4] and reading skills [5]. Likewise, prematurely born children have a higher frequency of health problems and functional limitations than peers born at term [6].…”
Section: Introductionmentioning
confidence: 99%
“…Transition to school is problematic for many children born preterm, as they have higher rates of learning disability, grade retention, special education needs, attention deficit disorder, behavior problems, and social emotional difficulties than fullterm peers [Bhutta et al, 2002;Aarnoudse-Moens et al, 2009b]. A number of studies have demonstrated improved cognitive, language, and reading scores with neuromaturation (i.e., developmental changes in brain function with age), most often in those without brain injury or neurosensory impairment, and in those raised in enriched environments (i.e., based on parental education, neighborhood characteristics, socioeconomic status) [Breslau et al, 2001;Ment et al, 2003;Hack et al, 2005;Samuelsson et al, 2006;Luu et al, 2009b;Claas et al, 2011]. Others report increasing rates of mild motor impairment, cognitive deficits, academic difficulties, and disability as children enter adolescence [Doyle and Casalaz, 2001;O'Brien et al, 2004;de Kieviet et al, 2009].…”
mentioning
confidence: 99%